Membumikan Nadhoman Tashrif Melalui Komunikasi Antarpersonal di Pondok Pesantren Roudlotul Mubtadi'in - Ahmad Nurul Khomari; Fatihatul Lailiyah (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2025)
Kitab Al-Amtsilah At-Tashrifiyah is a book that contains the rules of shorof science regarding examples of word changes in Arabic that must be memorized by students so that this knowledge is a requirement that must be met and understood by students in order to read the yellow book, but because Roudlotul Mubtadi'in Islamic Boarding School is a pesantren that prioritizes its students to memorize the Qur'an, the ustadz only told his students to chant nadhom tashrifan To hone the skills of the students in understanding the science of shorof. For this reason, the ustadz chose interpersonal communication in teaching his students by applying five interpersonal attitudes, namely openness, empathy, support, positive attitude, and equality. The purpose of this study was to determine the pattern of interpersonal communication built between ustadz and santri in grounding nadhom tashrifan at Roudlotul Mubtadi'in Islamic Boarding School. This study used qualitative descriptive method. The data collection process uses observation, interview, and documentation techniques using data analysis models from Miles & Huberman. The results of the study stated that of the five interpersonal communication attitudes that were most dominant in grounding nadhom tashrifan at Roudlotul Mubtadi'in Islamic Boarding School was the attitude of empathy and support of the ustadz towards his students which was shown by the ustadz who participated in chanting nadhom tashrifan for fifteen minutes before the start of the lesson.